Determination of Halogenide Salt Content in Solutions of Two Salts Using the Gravimetric Method: Penentuan Kadar Garam Halogenida pada Larutan Dua Garamnya dengan Metode Gravimetri - Darmawan, Petrus; Astuti Herawati, Dewi; Soebiyanto; Arif Wibawa, D. Andang (Jurnal Kimia dan Rekayasa, 2025)
So far, gravimetric analysis has always been carried out to analyze a particular substance in the form of a single substance. This method is very rarely used to analyze substances in mixture form and in the learning process in the laboratory. The aim of this research is to determine the levels of halogenide salts in solutions of two salts using the gravimetric method. The outline of this research is that a mixture of two halogenide salts is given a precipitating reactant and then gravimetric analysis is carried out, where the precipitate formed is weighed until a constant weight is obtained. The results of research analysis to determine the content of halogenide salts KBr and KCl using a sample volume of 20 ml obtained an average precipitate weight of 0.4001 g and a sample volume of 10 ml obtained an average precipitate weight of 0.2101 g. The average KCl content was 67.80% and the KBr content was 32.68% in a sample volume of 20 mL, while in a sample volume of 10 mL the KCl content was 71.49% and the KBr content was 28.56%. The average weight from stoichiometric calculations on a sample volume of 20 mL KCl is 7.43 g and KBr weighs 3.5854 g, likewise on a sample volume of 10 mL the average weight of KCl is 7.847 g and KBr is 3.133 g. Based on statistical test analysis using the independent sample t test, it shows that there is no real difference in taking 2 different sample volumes. AbstrakAnalisis gravimetri selama ini selalu dilakukan untuk menganalisis suatu zat tertentu dalam bentuk zat tunggal. Metode ini sangat jarang digunakan untuk menganalisis zat dalam bentuk campuran dan pada proses pembelajaran di laboratorium. Tujuan penelitian ini adalah untuk menetapkan kadar garam halogenida pada larutan dua garamnya dengan metode gravimetri. Garis besar penelitian ini adalah larutan campuran dua garam halogenida diberikan reaktan pengendap kemudian dilakukan analisis gravimetri, dimana endapan yang terbentuk ditimbang sampai diperoleh bobot konstan. Hasil penelitian analisis penetapan kadar garam halogenida KBr dan KCl menggunakan volume sampel 20 ml diperoleh bobot endapan rata-rata 0,4001 g dan pada volume sampel 10 ml didapatkan bobot endapan rata-rata 0,2101 g. Kadar KCl rata-rata sebesar 67,80% dan kadar KBr sebesar 32,68% pada volume sampel 20 mL, sedangkan pada volume sampel 10mL diperoleh kadar KCl 71,49% dan Kadar KBr 28,56%. Bobot rata-rata dari perhitungan stoikiometri pada volume sampel 20 mL KCl 7,43 g dan bobot KBr 3,5854 g, demikian juga pada volume sampel 10 mL bobot rata-rata KCl 7,847g dan KBr 3,133 g. Berdasarkan analisis uji statistik menggunakan independent sample t test menunjukkan bahwa tidak ada beda nyata pada pengambilan 2 volume sampel yang berbeda.